2017
DOI: 10.1111/psyp.12826
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acute stress on response inhibition in healthy men: An ERP study

Abstract: The current study investigated the influence of acute stress and the resulting cortisol increase on response inhibition and its underlying cortical processes, using EEG. Before and after an acute stressor or a control condition, 39 healthy men performed a go/no-go task while ERPs (N2, P3), reaction times, errors, and salivary cortisol were measured. Acute stress impaired neither accuracy nor reaction times, but differentially affected the neural correlates of response inhibition; namely, stress led to enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 91 publications
4
28
2
1
Order By: Relevance
“…Our findings contrast those of Wu et al (2017); however, in relation to their theory, the smaller Pe in our sample may indicate lower awareness of errors with greater stress. One primary difference between the current study and that of Wu et al (2017) (as well as Dierolf et al, 2017Dierolf et al, , 2018 is that their sample consisted of only males while ours had both males and females. Also, Wu et al (2017) used a within-subjects design with a baseline measure; our study compared between subjects having two groups.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Our findings contrast those of Wu et al (2017); however, in relation to their theory, the smaller Pe in our sample may indicate lower awareness of errors with greater stress. One primary difference between the current study and that of Wu et al (2017) (as well as Dierolf et al, 2017Dierolf et al, , 2018 is that their sample consisted of only males while ours had both males and females. Also, Wu et al (2017) used a within-subjects design with a baseline measure; our study compared between subjects having two groups.…”
Section: Discussioncontrasting
confidence: 61%
“…Reflections of inhibitory control as manifest by the N2 also suggest enhanced (i.e., more negative) amplitude during stressful conditions, whether the stress condition is a mental arithmetic task or avoiding shock (Ishida, 2006;Dierolf et al, 2017Dierolf et al, , 2018Qi et al, 2017Qi et al, , 2018. The larger N2 with the stress conditions in these studies were attributed to enhanced cognitive control process, reallocation of cognitive resources to processes of inhibitory control, and a coping strategy to focus attention on threatening information.…”
Section: Introductionmentioning
confidence: 55%
“…Figure 2 depicts the impact of the stress manipulation on subjective stress ratings (a) and cortisol (b). The proportion of participants in the stress condition who demonstrated a cortisol response to the stressor was 44%, which is slightly below studies using the gold standard laboratory stress manipulation, the Trier Social Stress Test (e.g., Engert et al, 2013;Kudielka, Kirschbaum, & Hellhammer, 2007), but is similar to studies involving laboratory stress manipulations in imaging contexts (e.g., Dierolf, Fechtner, Bohnke, Wolf, & Naumann, 2017;Pruessner et al, 2008). It is important to note, however, that we may not have captured the peak cortisol response in this sample (i.e., cortisol may have continued to increase beyond saliva sample 7; see Figure 2b) and 2.5 nmol/L may be an overly conservative threshold (Miller et al, 2013); therefore, the proportion of participants who demonstrated a cortisol response reported here may be an underestimation.…”
Section: Manipulation Check and Random Assignmentmentioning
confidence: 60%
“…MPFC (Harrivel et al, 2013;Durantin et al, 2015) DLPFC (Harrivel et al, 2013) DLPFC (Durantin et al, 2014;Fairclough et al, 2019) Left PFC (Kalia et al, 2018) occipital lobe (Kojima and Suzuki, 2010) EEG α power over occipital sites (Gouraud et al, 2018) (α and (β power (auditory stimuli) (Braboszcz and Delorme, 2011) (θ power (auditory stimuli) (Braboszcz and Delorme, 2011) N1 (Kam et al, 2011) N4 (O'Connell et al, 2009) P1 (Kam et al, 2011) P2 (Braboszcz and Delorme, 2011) P3 (Schooler et al, 2011) frontal θ power (Gärtner et al, 2014) P3 (Dierolf et al, 2017) frontal (θ power and parietal (α power (Ewing et al, 2016;Fairclough and Ewing, 2017) Event Related Coherence between midfrontal and right-frontal electrodes (Carrillo-De-La-Pena and García-Larrea, 2007) (α band power (Mathewson et al, 2009) P1 (Pourtois et al, 2006;Mathewson et al, 2009) P2 (Mathewson et al, 2009) N170 (Pourtois et al, 2006) P3 (Pourtois et al, 2006;Mathewson et al, 2009) N1 (Callan et al, 2018;Dehais et al, 2019a,b) P3 (Puschmann et al, 2013;Scannella et al, 2013;Giraudet et al, 2015b;Dehais et al, 2019a,b) (α power in IFG (Dehais et al, 2...…”
Section: Adaptation Of the User Interfacementioning
confidence: 99%